Analisis Faktor Determinan Vaginosis Bakterial secara Retrospektif di RSUD Dr. Saiful Anwar Malang Tahun 2012-2016 - Anna Fathiah; Nour Athiroh; Hari Santoso (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2018)
Most of the world's female population suffers from Bacterial Vaginitis characterized by changes in the normal vaginal flora replaced by anaerobic bacteria and facultative bacteria. Bacterial vaginitis increases the risk of STIs, abortion events, preterm labor, low birth weight, premature rupture of membranes and postpartum endometritis. It takes a retrospective study to determine the determinant factors that affect the population of Bacterial Vaginosis. The method this research using descriptive epidemiology and using retrospective approach, with observational research design. Secondary data were obtained from medical records of Obgyn Outpatient, with supporting data from Vulvovaginal Preparation Test. The place of research is done in the Medical Record Section. The population was all patients enrolled in the Obgyn of Outpatient Care Unit. The study sample was taken from patients diagnosed Bacterial Vaginitis in the period January 2012-December 2016. The results of the study, there were 50 cases of Bacterial Vaginitis. Determinant factors affecting Bacterial Vaginitis population in are age factor with range of 25-44 years (62%), patients with high school education status (16%), then patients with employment status as private workers and married status (88% ). Keywords : Bacterial vaginitis, Determinant Factor, Retrospective ABSTRAK Sebagian besar populasi wanita di dunia menderita Vaginosis Bakterial yang ditandai dengan perubahan flora normal vagina diganti dengan bakteri anaerob dan bakteri fakultatif.Vaginosis Bakterial meningkatkan resiko infeksi menular seksual, kejadian abortus, persalinan prematur, berat bayi lahir rendah, ketuban pecah dini dan endometritis postpartum. Sehingga diperlukan penelitian retrospektif untuk mengetahui faktor determinan yang berpengaruh terhadap populasi Vaginosis Bakterial. Metode penelitian ini adalah epidemiologi deskriptif menggunakan pendekatan retrospektif, dengan desain penelitian observasional. Data sekunder diperoleh dari catatan rekam medik pasien Unit Rawat Jalan Obgyn, dengan data pendukung dari hasil Tes Vulvovaginal Preparat. Populasi ialah semua pasien yang terdaftar dalam Unit Rawat Jalan Poliklinik Obgyn. Sampelpenelitian diambil dari pasien yang didiagnosis Vaginosis Bakterial pada periode Januari 2012-Desember 2016. Dari hasil penelitian ditemukan kejadian vaginosis bakterial sebanyak 50 kasus. Faktor determinan yang berpengaruh terhadap populasi yaitu faktor umur dengan kisaran 25-44 tahun (62%), pasien dengan status pendidikan tingkat SMA (16%), kemudian pasien dengan status pekerjaan sebagai pekerja swasta dan pasien berstatus telah menikah (88%). Kata kunci : Faktor Determinan,Vaginosis Bakterial, Retrospektif